Anatomical modifications, viviparous reproduction and hydraulic expulsion of larvae by Cephenemyia nasopharyngeal bot flies of deer. Issue 4 (14th March 2013) - ANDERSON, J. R.
Abstract : Several specialized adaptations of the reproductive and respiratory systems associated with the retention and expulsion of larvae in ovoviviparous Cephenemyia species (Diptera: Oestridae) are described and illustrated. In these flies the anterior section of the common oviduct is modified into a large sac‐like uterus that contains larvae, and the posterior section is modified into a larvipositor with a central tubular vagina. During larviposition, contraction of abdominal muscles forces haemolymph into a perivaginal sinus, causing a hydraulically driven exsertion of the larvipositor. A group of larvae and uterine fluid sealed off within the lumen of the vagina are then expelled from the vulva via hydraulic pressure as the stretched vagina is compressed. A one‐way, non‐return valve between the uterus and vagina prevents a reflux of larvae upward into the uterus during larviposition. All mutually dependent actions associated with larviposition occur almost simultaneously. All species have evolved a similar mechanism of expelling their larvae, but the shape of the non‐return valve is different in each species studied.